On the Subject of Scientific Communism and Its Laws - Davidavičius, Matas (Problemos, 1984)
Proceeding from the existing conception on the object of Scientific Communism as a science on socio-economic laws of communist formation, its origin, making, functioning and development, the contents of the concepts “social relations”, “social-political laws” are analysed by the author who arrives at a conclusion that the subject of Scientific Communism is not limited to the study of the above laws. Further, the author specifies the contents of laws of the development of the communist formation. Scientific Communism, as the author sees it, is the science on sociological laws of the origin, making, functioning, and development of the communist social formation.